Ratio Legis Investigation by the Prosecutor: A Review of Distribution of Power in Investigation of Corruption Crime - Abidin, R.B. Muhammad Zainal (Universitas Airlangga, 2024)
AbstractThis study discusses the distribution of investigative powers in the context of law enforcement on corruption crime. The urgency in this research that is to be achieved is to know the concept of distribution of investigative power in the field of corruption crime and to know the law with a closer distance to the ratio legis the Prosecutor is given the authority to investigate corruption crimes. The preparation of this research uses legal research by analyzing legislation as well as treatises on discussing the draft act which arrange institutions are authorized to investigate corruption crime. The results of this study indicate that in a lex specialis manner, those authorized to investigate corruption crime are investigators at the Prosecutor and the Corruption Crime Eradication Commission, in addition to investigators at the Police institution who are also authorized to investigate corruption crime in a lex generalis manner. The three institutions are equally authorized to investigate corruption crime based on the concept of cooperating with each other. The ratio legis forming the act when discussing the draft act number 16 of 2004 concerning the Prosecutor's Office gives the Prosecutor authority to investigate corruption crime, namely that people have high hopes for the prosecutor's office as one of the important pillars in upholding the supremacy of law and being pro-actively involved in eradicating rampant corruption crime in all areas of life, bearing in mind that corruptors in Indonesia at that time were experts in breaking into banks, taking state money abroad for the sole reason of seeking treatment abroad, destroying evidence, manipulating data, and being able to trick prosecutors into going abroad freely. The people's high hopes for the Prosecutor are based on Rousseau's social contract theory in the making of the act.Keywords: Distribution of Power; Investigation; Corruption Crime.